2004
DOI: 10.1038/sj.eye.6701438
|View full text |Cite
|
Sign up to set email alerts
|

Exudative age-related macular degeneration treated by intravitreal triamcinolone acetonide. A prospective comparative nonrandomized study

Abstract: Exudative agerelated macular degeneration treated by intravitreal triamcinolone acetonide. A prospective comparative nonrandomized study JB Jonas, RF Degenring, I Kreissig, T Friedemann and I Akkoyun Abstract Purpose To report on visual outcome of patients receiving an intravitreal injection of triamcinolone acetonide as treatment of progressive exudative age-related macular degeneration. Methods The prospective comparative nonrandomized clinical interventional study included 187 consecutive patients with prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
4

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 46 publications
3
46
0
4
Order By: Relevance
“…15 Considering that the patients included in the present study complained about a progressive loss of vision prior to the injection, the results of the present study are also in agreement with another study from the same group of authors in which patients receiving an intravitreal injection of triamcinolone acetonide performed significantly better than patients of a nonrandomized control group; and the results of the present study are in agreement with another investigation in which the injected eyes had a significantly better outcome than the contralateral nontreated eyes in patients with bilateral exudative age-related macular degeneration. 18,20 Comparing the results obtained at 6 months and at 12 months after the injection in present study with results reported for a combined treatment of intravitreal triamcinolone acetonide and verteporfin photodynamic therapy suggests that the combined treatment may be superior to the intravitreal triamcinolone acetonide monotherapy. 16,[30][31][32][33][34][35] Spaide et al 16 were the first to report on the combination of intravitreal triamcinolone acetonide with photodynamic therapy as treatment of exudative age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…15 Considering that the patients included in the present study complained about a progressive loss of vision prior to the injection, the results of the present study are also in agreement with another study from the same group of authors in which patients receiving an intravitreal injection of triamcinolone acetonide performed significantly better than patients of a nonrandomized control group; and the results of the present study are in agreement with another investigation in which the injected eyes had a significantly better outcome than the contralateral nontreated eyes in patients with bilateral exudative age-related macular degeneration. 18,20 Comparing the results obtained at 6 months and at 12 months after the injection in present study with results reported for a combined treatment of intravitreal triamcinolone acetonide and verteporfin photodynamic therapy suggests that the combined treatment may be superior to the intravitreal triamcinolone acetonide monotherapy. 16,[30][31][32][33][34][35] Spaide et al 16 were the first to report on the combination of intravitreal triamcinolone acetonide with photodynamic therapy as treatment of exudative age-related macular degeneration.…”
Section: Discussionmentioning
confidence: 55%
“…The studies have not been conclusive about the therapeutic value of intravitreal triamcinolone acetonide for treatment of exudative age-related macular degeneration. Some small-scaled case-series investigations using the dosage of about 20 mg triamcinolone acetonide reported a beneficial effect 11,15,18,20 contradicting a previous randomized clinical trial using a dosage of 4 mg triamcinolone acetonide. 14 In view of the different results of the previous investigations and different dosages used, it was the purpose of the present consecutive case-series study to assess in a longer followup patients who had received an intravitreal high-dosage injection of triamcinolone acetonide.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…All patients received an intravitreal high-dose injection of triamcinolone acetonide of about 20 mg as single and only procedure and had been evaluated in previous single-disease studies. 6,7,14,18,21,26,30,45,46,8 Age was significantly lowest in the uveitis group than in the other groups. 0.042).…”
Section: Introductionmentioning
confidence: 91%
“…Following Robert Machemer, Gholam Peyman, and others, [1][2][3][4][5][6] intravitreal triamcinolone acetonide has increasingly been used in recent studies as treatment for other intraocular proliferative, oedematous, and neovascular diseases, such as diffuse diabetic macular oedema, [7][8][9][10][11][12][13] central retinal vein occlusion, [14][15][16][17] branch retinal vein occlusion, [18][19][20] chronic uveitis, [21][22][23][24][25] persistent pseudophakic cystoid macular oedema, [26][27][28][29] exudative age-related macular degeneration, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and other diseases. 6 It has remained unclear so far, whether the various ocular disorders differ in their response to intravitreal triamcinolone acetonide in terms of an increase in visual acuity and a rise in intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%